Mengintegrasikan budaya dalam pembelajaran matematika kontekstual: strategi peningkatan kemampuan numerasi siswa sekolah dasar - Afifah, Putri Nur; Faizah, Hanim (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study addresses deficient numeracy literacy among elementary students by implementing a local culture-based Contextual Teaching and Learning (CTL) model, utilizing the traditional